Mapping Workplace Inclusion in Hierarchical Collectivist Societies: A Causal Loop Diagram Approach - Toronata Tambun; Gatot Yudoko; Leo Aldianto (Systems)
Workplace integration in hierarchical collectivist societies is shaped by structured social mechanisms rather than collectivist values alone. While collectivism is often assumed to foster inclusiveness, its structural manifestations regulate workplace inclusion through feedback loops of hierarchical loyalty, trust building, and kinship-based exclusivity. This study employs causal loop diagrams (CLDs) to conceptually map how cultural structures regulate workplace inclusion—not to assert empirical causality, but to illustrate the culturally grounded feedback loops in Indonesia and the Philippines. The findings identify the reinforcing loops that sustain hierarchical exclusivity in Indonesia and a counterbalancing loop that facilitates immediate kinship-based trust in the Philippines. By conceptualizing workplace inclusion as an emergent property of interdependent social mechanisms, this study highlights how structured exclusivity stabilizes hierarchical workplaces while limiting adaptability. Unlike frameworks that treat collectivism as a static cultural trait, CLDs provide a dynamic lens to analyze how workplace inclusion evolves through structured feedback loops—revealing how structured exclusivity in collectivist systems governs trust, inclusion, and legitimacy not through ideology alone, but through relational sponsorship, time-dependent trust, and group-based gatekeeping. These insights contribute to cross-cultural management and organizational studies by demonstrating how structured exclusion functions as a self-reinforcing mechanism. The findings have implications for multinational corporations, policymakers, and organizational leaders seeking to design adaptive strategies for workplace integration in hierarchical collectivist environments. While both countries are analyzed, Indonesia serves as the primary site of investigation, with the Philippines providing a contrast to illuminate structured exclusivity mechanisms in hierarchical collectivist contexts.